DAMPAK AKTIVITAS FISIK PADA PENINGKATAN KESEHATAN TULANG PADA REMAJA : STUDI LITERATUR - Muhammad Akbar Syafruddin; Nur Indah Atifah Anwar (STKIP Melawi, 2026)
This study uses a literature review method to analyze and synthesize information from various studies that have been conducted related to the impact of physical activity on adolescent bone health. The data used in this study came from scientific journals, research articles, books, and reports published in the last 10 years. Data was taken from trusted academic platforms such as PubMed, ScienceDirect, Google Scholar, and national journal portals such as Garuda. Data was collected using certain keywords such as